Krewe of Hunters: Seeing Darkness - Book 30 - Graham, Heather (Toronto, Ontario, Canada : Mira, 2020)
It was supposed to be a fun girls weekend in Salem, but when a past-life regression session instead sends a terrifying vision of murder to Kylie Connelly, shes shaken and doesnt know what to think. Worse, later she identifies the attacker from her vision: hes a prominent local politician. Special Agent Jon Dickson of the FBIs Krewe of Hunters is on the trail of a suspected serial killer based on the scantest of clues and unreliable witness testimony. When he realises Kylies vision might be his best lead, he must gain her trust and get close enough to guide her new talent. Though she doubts herself, the danger Kylie sees is all too real-and the pair will have to navigate a murderers twisted passions and deceptions to stop the killer from claiming another victim.
Keywords: United States -- Federal Bureau of Investigation -- Fiction; Government investigators -- United States; Fiction; Reincarnation therapy -- Fiction; Extrasensory perception -- Fiction; Murder -- Investigation; Fiction; Serial murderers -- Fiction; Salem (Mass.) -- Fiction; Thriller; Romance fiction; Detective and mystery fiction